Percutaneous balloon valvuloplasty for management of pulmonic stenosis in four dogs: First experience in Veterinary Medicine in Romania - Florin Leca; Altin Cala; Stefan Adrian Geanta; Mihaela Claudia Ivanciu; Alina Nechifor; Ana Maria Vlas; Luigi Venco (Cluj Veterinary Journal, 2025)
Pulmonic stenosis (PS) is one of the most common congenital heart diseases (CHD) in dogs, accounting for approximately 32% of all congenital cardiac defects diagnosed in this species [9]. If severe and left undiagnosed or untreated, PS can lead to signs of right-sided congestive heart failure (R-CHF) and, ultimately, death [7]. This paper describes aspects of the palliative management of PS using percutaneous balloon valvuloplasty (BVP) in four dogs, which, to the authors' knowledge, has not been previously performed in Romania. The minimally invasive procedures were performed between December 2021 and February 2023, at the first Interventional Veterinary Radiology Laboratory in Romania., specialized and optimised for Interventional Veterinary Cardiology (Doctor's Vet Univers Clinic, Bucharest). All patients were referred for signs of exercise intolerance or syncope due to haemodinamic effects of PS. The population included 2 females and 2 males aged between 18 and 72 months. Three dogs who underwent BVP showed a reduction in pressure gradient between 28 and 50 percent and a positive outcome. In one dog, the BPV failed to reduce the pressure gradient, and the patient subsequently suffered a sudden cardiac death (SCD). These findings are comparable with previously reported data in the literature and support the use of BVP as an effective palliative option for managing PS in dogs. Although the learning curve is important for improving outcomes, continued experience remains crucial for achieving consistent success.